Marie Visser: eerste Bloemfonteinse vrouestadsraadslid - Haasbroek, Hannes (National Museum, 2016)
Marie Visser - First Bloemfontein woman to be elected Town Counciller. Although several women endeavoured to gain a seat on the Bloemfontein Town Council, Marie Visser was the first to be elected, in 1932. This was due to the amendment of the municipal ordinance in 1929 that made provision for the plural vote, by which wives whose husbands had sufficient property qualification were eligible to vote and stand as councillors. Visser was successful only after three previous attempts, when she won in a by-election. She served on the Town Council until 1939 when she retired.
Keywords: Marie Magdalena Elizabeth Visser; National Museum, Bloemfontein; Culna; Town council